Modulation of phenolic metabolism under stress conditions in a Lotus japonicus mutant lacking plastidic glutamine synthetase - García-Calderón, Margarita; Pons-Ferrer, Teresa; Mrazova, Anna; Pal'Ove-Balang, Peter; Vilkova, Maria; Pérez-Delgado, Carmen M.; Vega, José M.; Eliašová, Adriana; Repčák, Miroslav; Márquez, Antonio J.; Betti, Marco (Frontiers in Plant Science, 2015)
This paper was aimed to investigate the possible implications of the lack of plastidic glutamine synthetase (GS2) in phenolic metabolism during stress responses in the model legume Lotus japonicus. Important changes in the transcriptome were detected in a GS2 mutant called Ljgln2-2, compared to the wild type, in response to two separate stress conditions, such as drought or the result of the impairment of the photorespiratory cycle. Detailed transcriptomic analysis showed that the biosynthesis of phenolic compounds was affected in the mutant plants in these two different types of stress situations. For this reason, the genes and metabolites related to this metabolic route were further investigated using a combined approach of gene expression analysis and metabolite profiling. A high induction of the expression of several genes for the biosynthesis of different branches of the phenolic biosynthetic pathway was detected by qRT-PCR. The extent of induction was always higher in Ljgln2-2, probably reflecting the higher stress levels present in this genotype. This was paralleled by accumulation of several kaempferol and quercetine glycosides, some of them described for the first time in L. japonicus, and of high levels of the isoflavonoid vestitol. The results obtained indicate that the absence of GS2 affects different aspects of phenolic metabolism in L .japonicus plants in response to stress.